Urban wastewater: a valuable resource for agriculture: a case study from Haroonabad, Pakistan - Hoek, Wim van der; Ul-Hassan, Mehmood; Ensink, Jeroen H.J.; Feenstra, S.; Raschid-Sally, Liqa; Munir, S.; Aslam, R.; Ali, N.; Hussain, R.; Matsuno, Y. (International Water Management Institute, 2002)
Farming communities in water-scarce regions increasingly practice the use of urban wastewater in agriculture. Untreated urban wastewater is generally considered unacceptable for direct use because of potential health risks. However, in many parts of the world, poor farmers in peri-urban areas use untreated wastewater. This situation is considered likely to continue even in the foreseeable future due to the high investment cost associated with the installation of treatment facilities.